Education Mapping As a Reference Village Program in Cigadung, Brebes Regency Through Sistem Informasi Pembangunan Berbasis Masyarakat (SIPBM) - Latiana , Lita; Hidayah, Isti (KnE Social Sciences, 2019)
The mandate of the Child Protection Act Article 9 states that every child has the right to receive education and teaching in the context of his personal development and the levelofhisintelligenceinaccordancewithhisinterestsandtalents.Childrenunderthe age of 18 in Cigadung Village are around 28% of the total population in the village. Therefore, the government or community has the responsibility to provide education services for school-age children. Based on this background, the problem in this study are1)Howistheconditionofaccesstoeducationservicesforchildrenaged6-18years in Cigadung Village?; and 2) How is the alternative program for school-age children in accordance with the results of the SIPBM application?. This research is a descriptive study by analyzing data quantitatively and qualitatively. In this case the research subjectwasthefamilyheadoftheCigadungVillage.Dataretrievalisdonebyinterview method and documentation. While the data that has been obtained will be narrated. The results of the study showed that a 564 out of a total of 1216 school-aged children were served access to education. Thus, there are around 53% of school-aged children in Cigadung Village who have not attended school. The top three factors that cause these children not to go to school are the perceived better work, economic burden and better assumption of marriage. Meanwhile, several alternative programs that are in accordancewith the SIPBM applicationnamely GerakanKembali Bersekolah,Forum Masyarakat Peduli Pendidikan Desa and “Kejar Paket”. Keywords: Access of education, SIPBM, school age children